2009
DOI: 10.1016/j.otohns.2009.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of deep neck space abscesses

Abstract: Substance abuse and poor orodental hygiene are important predisposing factors to deep neck abscesses. Appropriate management continues to favor a combination of early surgical drainage and systemic antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 24 publications
5
79
0
10
Order By: Relevance
“…Fewer patients referred to problems such as functional limitation, physical disability, or handicap. (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) years in the present study population; Fig. 1).…”
Section: Patients' Age Distribution (Years)mentioning
confidence: 77%
“…Fewer patients referred to problems such as functional limitation, physical disability, or handicap. (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) years in the present study population; Fig. 1).…”
Section: Patients' Age Distribution (Years)mentioning
confidence: 77%
“…Other reported complications of disseminating dental infections include brain abscess (21)(22)(23)(24), septicemia in a patient with multiple myeloma (25), deep neck infection (26,27), mediastinitis (14,(28)(29)(30), necrotizing fasciitis (31)(32)(33), orbital abscess (34)(35)(36), and cervical spondylodiscitis with spinal epidural abscess (37). It has been suggested that some host-related factors may contribute toward increased morbidity and mortality associated with acute dental abscesses, including diabetes, chronic alcohol and tobacco consumption, malnourishment, and the use of illicit substances (26,27,33).…”
Section: Complications Stemming From Acute Apical Abscessesmentioning
confidence: 99%
“…It has been suggested that some host-related factors may contribute toward increased morbidity and mortality associated with acute dental abscesses, including diabetes, chronic alcohol and tobacco consumption, malnourishment, and the use of illicit substances (26,27,33).…”
Section: Complications Stemming From Acute Apical Abscessesmentioning
confidence: 99%
“…21 It plays a crucial role in shaping the involved areas and monitoring the development of the infection, with the intent to plan the proper surgical approach. [22][23][24] Ultrasound is another useful method in guiding diagnostic needle aspiration and therapeutic drainage, in cases where there is no immediate airway compromise. In two cases, percutaneous drainage under ultrasound guidance was performed.…”
Section: Discussionmentioning
confidence: 99%